Pengaruh Lingkungan Kerja Non Fisik dan Disiplin Kerja Terhadap Kepuasan Kerja Pegawai pada Kantor Camat Palibelo Kabupaten Bima - Vivi Sumanti; Firmansyah Kusumayadi (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2021)
This study aims to determine the effect of non-physical work environment and work discipline on employee job satisfaction at the Palibelo Sub-district Office, Bima Regency. The type of research determined is explanatory research with a quantitative approach. The data sources in this study are primary data. This study is a population study with 35 respondents at the Palibelo Subdistrict Office, Bima Regency. The sampling technique used is saturated sampling (total population). The technique of collecting research data is using the questionnaire method. Methods of data analysis using validity and reliability tests, classical assumptions, multiple linear regression. Correlation coefficient, significance test using T test and F test with a significance level of 5%. The results showed that non-physical work environment variables had a significant effect and showed positive results on employee job satisfaction. The work discipline variable has a positive and insignificant effect on employee job satisfaction. The results of the test and analysis show that F count > F table or 6.781 > 3.27 and a significance value < 0.05 or 0.004 < 0.05, so there is a simultaneous influence of non-physical work environment and work discipline on employee job satisfaction. This is evidenced by the correlation coefficient (R) of 0.546 or 54.6%, meaning 54.6% of the contribution or influence of non-physical work environment variables (X1) and work discipline (X2) simultaneously (together) on the variable Job satisfaction (Y), while the remaining 45.4% is the influence of other factors not examined.